Implications of aphid flight patterns for pest management of potatoes - Stufkens, M.A.W.; Teulon, D.A.J.; Nicol, D.; Fletcher, J.D. (New Zealand Plant Protection, 2000)
The flight patterns of aphid vectors of the potato leaf roll virus were monitored for 18 years with a 75 m high suction trap at Lincoln Canterbury Analysis of the collected samples indicates that latespring and autumn aphid flight peaks vary considerably between seasons and years in their timing magnitude and duration which may have important implications for aphid and virus control in potato crops The potential of a virus forecasting system based on aphid flight monitoring to support potato growers pest management decisions is discussed